RANCANG BANGUN MODEL USAHATANI KONSERVASI SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS LAHAN KERING - Rupa Matheus (Partner, 2009)
Model Plan Usahatani Conservation As Dry Farming ProductivityEnhanced Efforts. In the effort erosion trouble-shooting and the low of dry farming productivity, has been executed serangkian research which in focussed in area of Praktek Politani Kupang having location in Oesao Kabupaten Kupang. Research aim to study specific usahatani model of dry farming. Three kinds of model usahatani conservation has been checked, yakti bench terrace, terrace;core gulud and without terrace;core. Measurement of level of erosion is done in emperis with method USLE. To evaluate farm productivity also is done cultivation of green peanut crop Result of research indicates that technically, model usahatani conservation of bench terrace and terrace;core gulud gives repair impact to degradation of erosion speed and improvement of farm productivity. Bench terrace earns effectively lessens erosion until under admissible erosion boundary, however memerlukn technical clauses in its(the making in order not to harm plant growth. Terrace;core gulud is one of alternative of conservation that need to be considered, especially at soil;land;grounds having [shallow/ superficial] solum, because cost in its(the making is cheap and doesn't require many labours, and top layer soil is not annoyed. Key word: Farming of Conservation, Dry farming Productivity